Protected stent retriever thrombectomy prevents iatrogenic emboli in new vascular territories - Klinger-Gratz, Pascal P. (Neuroradiology, 2015)
INTRODUCTION: Diagnostic tools to show emboli reliably and protection techniques against embolization when employing stent retrievers are necessary to improve endovascular stroke therapy. The aim of the present study was to investigate iatrogenic emboli using susceptibility-weighted imaging (SWI) in an open series of patients who had been treated with stent retriever thrombectomy using emboli protection techniques. METHODS: Patients with anterior circulation stroke examined with MRI before and after stent retriever thrombectomy were assessed for iatrogenic embolic events. Thrombectomy was performed in flow arrest and under aspiration using a balloon-mounted guiding catheter, a distal access catheter, or both. RESULTS: In 13 of 57 patients (22.8 %) post-interventional SWI sequences detected 16 microemboli. Three of them were associated with small ischemic lesions on diffusion-weighted imaging (DWI). None of the microemboli were located in a new vascular territory, none showed clinical signs, and all 13 patients have been rated as Thrombolysis in Cerebral Infarction (TICI) 2b (n = 3) or 3 (n = 10). Retrospective reevaluation of the digital subtraction angiography (DSA) detected discrete flow stagnation nearby the iatrogenic microemboli in four patients with a positive persistent collateral sign in one. CONCLUSION: Our study demonstrates two things: First, SWI seems to be more sensitive to detect emboli than DWI and DSA and, second, proximal or distal protected stent retriever thrombectomy seems to prevent iatrogenic embolization into new vascular territories during retraction of the thrombus, but not downstream during mobilization of the thrombus. Both techniques should be investigated and refined further.